Maturation of Heterogeneity in Afferent Synapse Ultrastructure in the Mouse Cochlea - Payne, Shelby A.; Joens, Matthew S.; Chung, Heather; Skigen, Natalie; Frank, Adam; Gattani, Sonali; Vaughn, Kya; Schwed, Allison; Nester, Matt; Bhattacharyya, Atri; Iyer, Guhan; Davis, Bethany; et al. (Frontiers in Synaptic Neuroscience, 2021)
Auditory nerve fibers (ANFs) innervating the same inner hair cell (IHC) may have identical frequency tuning but different sound response properties. In cat and guinea pig, ANF response properties correlate with afferent synapse morphology and position on the IHC, suggesting a causal structure-function relationship. In mice, this relationship has not been fully characterized. Here we measured the emergence of synaptic morphological heterogeneities during maturation of the C57BL/6J mouse cochlea by comparing postnatal day 17 (p17, ~3 days after hearing onset) with p34, when the mouse cochlea is mature. Using serial block face scanning electron microscopy and three-dimensional reconstruction we measured the size, shape, vesicle content, and position of 70 ribbon synapses from the mid-cochlea. Several features matured over late postnatal development. From p17 to p34, presynaptic densities (PDs) and post-synaptic densities (PSDs) became smaller on average (PDs: 0.75 to 0.33; PSDs: 0.58 to 0.31 µm2) and less round as their short axes shortened predominantly on the modiolar side, from 770 to 360 nm. Membrane-associated synaptic vesicles decreased in number from 53 to 30 per synapse from p17 to p34. Anatomical coupling, measured as PSD to ribbon distance, tightened predominantly on the pillar side. Ribbons became less spherical as long-axes lengthened only on the modiolar side of the IHC, from 372 to 541 nm. A decreasing gradient of synaptic ribbon size along the modiolar-pillar axis was detected only at p34 after aligning synapses of adjacent IHCs to a common reference frame (median volumes in nm3 x 106: modiolar 4.87; pillar 2.38). The number of ribbon-associated synaptic vesicles scaled with ribbon size (range 67 to 346 per synapse at p34), thus acquiring a modiolar-pillar gradient at p34, but overall medians were similar at p17 (120) and p34 (127), like ribbon surface area (0.36 vs 0.34 µm2). PD and PSD morphologies were tightly correlated to each other at individual synapses, more so at p34 than p17, but not to ribbon morphology. These observations suggest that PDs and PSDs mature according to different cues than ribbons, and that ribbon size may be more influenced by cues from the IHC than the surrounding tissue.